Detection of subtilisin 3 and 6 in skin biopsies of cattle with clinically manifested bovine ringworm. (21st October 2020) - Lindenhahn, Jakob; Bartosch, Theresa; Baumbach, Christina-Marie; Suchowski, Marcel; Kacza, Johannes; Schrödl, Wieland; Michler, Jule K
Abstract: Trichophyton ( T. ) verrucosum is a highly pathogenic dermatophyte causing zoonotic bovine ringworm that is transmissible to humans. The virulence factors subtilisin (Sub)3 and Sub6 are discussed to contribute to disease manifestation but no protein expression study is available for T. verrucosum . We used customized antibodies (against Trichophyton -species, Sub3 and Sub6) to examine skin biopsies of infected cattle via immunofluorescence stainings. Both virulence factors Sub3 and 6 were solely expressed by conidia and not only found in epidermal but also in dermal and hair structures. The anti-T-antibody reliably detected the fungus and proved more sensitive compared to histological stains. Lay Summary: We examined the zoonotic dermatophyte Trichophyton ( T. ) verrucosum in bovine skin and studied two important virulence factors called subtilisin (Sub)3 and Sub6 that T. verrucosum produces and secretes using immunolabeling.